The Effect of Leadership, Employee Engagement, and Self Learning on Effectiveness of Employee's Work: Human Resouce Management - Hasibuan, Paima Erianto; Akbar, Maruf; Suyanto, Thomas (International Journal of Scientific Research and Management (IJSRM), 2018)
Purpose - The aim of this article is to analysis, an organizational performance through process systematically to improve organizational performance through improving the performance of individuals and teams.Design / methodology / approach - This study, used survey method with quantitative approach, the instrument measuring instrument in the form of a questionnaire. This study population as many as 133 employees. Saturated sampling used in this study. The test instrument Carried out on 30 employees. Analysis was done by using descriptive and inferential statistics.Findings - The results show that Leadership has positive effect on Employee Effectiveness, Employee Engagement positively effect on Employee Effectiveness, Positive effect on the Independent Learning Employee Effectiveness, Leadership has positive effect on employee engagement, Leadership has positively effect on Self-egulated Learning and Employee Engagement positively affects Self-Learning.Practical implications - This study highlights the importance of providing support to Leadership, Employee Engagement, Self Learning and the effect on Effectiveness of Employee's Work.Keywords: Leadership, Engagement, Self-Learning, EffectivenessJEL: M0, M5